Application of Hungarian Algorithm for assigning workers in a garment company / Rossidah Wan Abdul Aziz ... [et al.] - Abdul Aziz, Rossidah Wan; Zolkefli, Nur Illiyana; Yaakob, Hazirah; Zamri, Nursafura Basyira (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Textiles and garment sector is one of Malaysia's most important industries, contributing significantly to its GDP through exports earnings. To become a piece of clothing, it must go through four stages: designing, fabric cutting, sewing, and packaging. The sewing line consists of a set of workstations where each worker at the station performs one to several operations. In this study, we modelled the workers-jobs allocation for a garment manufacturing company that engaged in the production of school uniforms as an assignment problem. There is a limited number of studies that demonstrate the relevance of the assignment model in the garment industry. According to Wulan et al. (2019), there are four methods that can be used to solve the assignment problems, which are Transportation method, Simplex method, Enumeration method and Hungarian method. However, they claimed that the Hungarian method is the best method in obtaining the optimal solution. Therefore, this study demonstrated the usefulness of the assignment model in workers' assignment to tasks in the garment company, and the focus was to minimize the time taken of garment production through worker’s assignment using the Hungarian Algorithm.